Takhrīj al-Ḥadīṡ sebagai Metode Analisis Historis: Integrasi Kritik Sanad, Matan, dan Konteks Sosial Periwayatan - Siregar, Idris; Sari, Friskila Santika; Putri, Aprilia; Siregar, Faliha Aulia; Siregar, Agung Julian (Yayasan Albahriah Jamiah Indonesia, 2025)
This article departs from the methodological problems in contemporary hadith studies that tend to reduce takhrīj al-Ḥadīṡ as a technical-verification procedure to assess the validity of the sanad, while ignoring the historical, discursive, and social dimensions of the hadith transmission process. This reduction causes analytical limitations in understanding hadith as a product of knowledge transmission that occurs in a specific spatial and temporal context. This study aims to reconstruct takhrīj al-Ḥadīṡ as an integrative historical analysis method by combining sanad criticism, matn criticism, and analysis of the social context of transmission within a single integrated methodological framework. This study uses a qualitative method with a historical-critical approach through a review of classical and contemporary hadith literature, a comparative analysis of transmission routes, and an examination of the relationship between hadith texts, narrators, and the socio-intellectual conditions that underlie them. The results of this study indicate that the integration of sanad criticism, matn criticism, and social context allows analysis of the reading of hadith not only as a static normative text, but as a dynamic historical process, reflecting the interaction between the authority of the narrators, social structures, and the epistemic needs of the early Muslim community. This approach reveals variations in redaction, shifts in meaning, and social rationalities that influence the selection and transmission of hadith. Theoretically, this study has implications for the development of contemporary hadith study methodology by expanding the function of takhrīj al-Ḥadīṡ from a verification tool to an instrument of historical analysis capable of bridging the classical critical tradition with modern scientific approaches.